The prospects for an economic community in north Africa: managing economic integration in the Maghreb states - Robana, Abderrahman (New York : Praeger, 1973)
This study seeks to evaluate the relevance of economic integration, in terms of both existing theory and actual practice, in the context of an underdeveloped region such as Maghreb.
Bibliography: p. 182-202.
osc 29/08/2018
Loans
Keywords: Africa, North